2011
DOI: 10.1002/atr.174
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing sustainable feeder bus operation considering realistic networks and heterogeneous demand

Abstract: A mathematical model is developed to optimize social and fiscal sustainable operation of a feeder bus system considering realistic network and heterogeneous demand. The objective total profit is a nonlinear, mixed integer function, which is maximized by optimizing the number of stops, headway, and fare. The stops are located which maximize the ridership. The demand elasticity for the bus service is dependent on passengers' access distance, wait time, in-vehicle time, and fare. An optimization algorithm is deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Chien [11] optimized bus size, route and headway that minimized total cost for a feeder service. DiJoseph and Chien [12] optimized stop locations, headway and fare that maximized total profit for a feeder bus service.…”
Section: A Transit Network Design (Tnd)mentioning
confidence: 99%
“…Chien [11] optimized bus size, route and headway that minimized total cost for a feeder service. DiJoseph and Chien [12] optimized stop locations, headway and fare that maximized total profit for a feeder bus service.…”
Section: A Transit Network Design (Tnd)mentioning
confidence: 99%
“…Mohaymany et al [28][29][30][31] enabled the network design to have various capacity and performance, and then introduced an ant colony algorithm to find better routes, which can attract more private car users to use public transport. Alshalaflah et al [32][33][34][35][36] studied the feasibility and advantages of using flexible route services instead of fixed connecting bus lines, and selected three lines in the suburb of Toronto with regional commuter rail lines for simulation. The result showed that it is significant to allocate appropriate slack time to provide effective flexible line service.…”
Section: Coordination and Optimization Of Rail And Public Transportmentioning
confidence: 99%
“…The transfers and connections between URT and buses is a popular research topic in passenger multimodal transport. The two main research areas are a) optimization of the layout of station or transfer facilities [6]- [8] and b) optimization of the lines or schedules of the bus for connecting to URT [9]- [12]. In view of the unexpected interruption of URT, Jin et al [13] proposed optimizing the bus-bridge service to better evacuate stranded passengers.…”
Section: Related Workmentioning
confidence: 99%